Pemberdayaan Santri Pondok Pesantren Al Firdaus Palembang Pada Era Industri 4.0 Melalui Literasi Digital Akad-akad Transaksi Syariah - Nur, Isnayati; Litriani, Erdah (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
The progress of the industrial revolution 4.0 demands public understanding of sharia transaction contracts amidst the growing growth of sharia business. This community service activity in the form of empowering students in the 4.0 era as a form of effort in digital literacy of sharia transaction contracts has not been widely carried out. This activity aims to provide literacy in the form of visual media about sharia transaction contracts. The method of this community service activity was carried out in the form of making a video of literacy of sharia banking contracts with several stages starting from the initial survey activity, planning, implementation to the evaluation stage. The result of this video making activity about the practice of sharia transaction contracts was that there is an increase in students' understanding of sharia transaction contracts before and after watching the video that has been made with the value 77% students understand sharia transaction contracts which the previous value 26%. This shows that audio-visual media in the form of videos makes it easier for students to understand the practice of sharia transaction contracts.